Soil systems (MDPI, 2018)
"Soil Systems is a new journal devoted to publishing articles focused on biological, chemical, and physical processes operating within soils and sediments. We are particularly interested in studies or review articles that examine (or describe) coupled processes operating within these complex media that control element cycling. Processes that impact on retention and release, transport, and microbial interactions in soils are also of interest"--About, viewed March 27, 2020.